Collaborating with artists to design additional multimodal and unimodal interaction techniques for three-dimensional drawing in virtual reality - Sullivan, Brian T., author; Ortega, Francisco, advisor; Ghosh, Sudipto, committee member; Tornatzky, Cyane, committee member; Barrera Machuca, Mayra, committee member; Batmaz, Anil Ufuk, committee member (Colorado State University. Libraries, 2023)
Although drawing is an old and common mode of human creativity and expression, virtual reality (VR) has presented an opportunity for a novel form of drawing. Instead of representing three-dimensional objects with marks on a two-dimensional surface, VR permits people to create three-dimensional (3D) drawings in midair. It remains unknown, however, what would constitute an optimal interface for 3D drawing in VR. This thesis helps to answer this question by describing a co-design study conducted with artists to identify desired multimodal and unimodal interaction techniques to incorporate into user interfaces for 3D VR drawing. Numerous modalities and interaction techniques were proposed in this study, which can inform future research into interaction techniques for this developing medium.
Keywords: human-computer interfaces; VR sketching; VR drawing; 3D art